A new Otocinclus (Siluriformes: Loricariidae: Hypoptopomatinae) from the Rio Juruena Basin, central Brazil - Ribeiro, Alexandre Cunha; Lehmann, Pablo A. (Zootaxa, 2016)
A new species of Otocinclus (Loricariidae) is described from the Rio Juruena, a right bank tributary of the Rio Tapajós system in Mato Grosso State, central Brazil. The new taxon can be distinguished from its congeners by the possession of an ocular operculum and by a complete lateral line. Additionally, the new species is distinguished by having a dorsal trunk coloration composed of a set of distinct oval dark blotches and by a caudal spot.